Abstracts from the European Respiratory Society Annual Conference 2018 on Thoracic Oncology - Bostantzoglou, Clementine; Iliopoulou, Marianthi; Blum, Torsten Gerriet (Journal of Thoracic Disease, 2018)
Lung cancer is the number one cause of death due to cancer worldwide. According to WHO, it accounts for 1.69 million new cases in 2015 (1), whereas in Europe 20.8% of all deaths due to cancer (over 266,000 cases) were attributable to lung cancer in 2011 (2).